TUMBUHAN SEBAGAI TANDA DALAM FOTOGRAFI JALANAN - Andri William (Saraswati)
The creation of works of art about the human and the plant, see the definition of the new form will sign from plants, found in streets is present as a result of the pattern of human behaviour, with the construction of different every day. by construction into the street photography.See the results of the construction of the plant as a marker in a street photography is not just as a silent picture.With no sign of man cannot communicate, study of the coat of arms (including sign) that represents the object (objects, ideas, feelings, situations, circumstances) out of him. This concept is integrated in many theories related to the language, discourse, and non verbal activities. The meaning arises from the triangular relationship (triad of meaning): object (referent), mind (reference), and the coat of arms semantic knowledge , about the direct relationship between symbol and its object. A dictionary is a book reference sematic. Sintaktika, about the relationship between coat of arms. Coat of arms does not stand alone, but rather with other symbols, in a larger symbol system called code. Here, the symbol can be verbal or non-verbal. Pragmatics, about the practical usefulness of the human in the midst of a particular culture. From the perspective of semiotics, for successful communication is not enough to understand the symbols separately, but also grammar (Syntax) which regulates the relationships between patterns-coat of arms, as well as culturalPhotography was present to record the memories of the incident or the memory of its history in a particular space that never experienced and known or he believes at a given time. street photography is a portrait of a social community of the city. Messages that it contains also have social mission and invite others to ponder the meaning behind such works. Nevertheless, it is precisely not a few of the perpetrators of street photography is thus viewed it as their personal papers make it for personal ambitions for the sake of satisfaction in creating the work.Keywords: human, plants, signs and street photography